Copper-coordinated cellulose ion conductors for solid-state batteries - Yang, Chunpeng; Wu, Qisheng; Xie, Weiqi; Zhang, Xin; Brozena, Alexandra; Zheng, Jin; Garaga, Mounesha N.; Ko, Byung Hee; Mao, Yimin; He, Shuaiming; Gao, Yue; Wang, Pengbo; et al. (Nature (London), 2021)
Although solid-state lithium (Li)-metal batteries promise both high energy density and safety, existing solid ion conductors fail to satisfy the rigorous requirements of battery operations. Inorganic ion conductors allow fast ion transport, but their rigid and brittle nature prevents good interfacial contact with electrodes. Conversely, polymer ion conductors that are Li-metal-stable usually provide better interfacial compatibility and mechanical tolerance, but typically suffer from inferior ionic conductivity owing to the coupling of the ion transport with the motion of the polymer chains 1 – 3 . Here we report a general strategy for achieving high-performance solid polymer ion conductors by engineering of molecular channels. Through the coordination of copper ions (Cu 2+ ) with one-dimensional cellulose nanofibrils, we show that the opening of molecular channels within the normally ion-insulating cellulose enables rapid transport of Li + ions along the polymer chains. In addition to high Li + conductivity (1.5 × 10 −3 siemens per centimetre at room temperature along the molecular chain direction), the Cu 2+ -coordinated cellulose ion conductor also exhibits a high transference number (0.78, compared with 0.2–0.5 in other polymers 2 ) and a wide window of electrochemical stability (0–4.5 volts) that can accommodate both the Li-metal anode and high-voltage cathodes. This one-dimensional ion conductor also allows ion percolation in thick LiFePO 4 solid-state cathodes for application in batteries with a high energy density. Furthermore, we have verified the universality of this molecular-channel engineering approach with other polymers and cations, achieving similarly high conductivities, with implications that could go beyond safe, high-performance solid-state batteries. By coordinating copper ions with the oxygen-containing groups of cellulose nanofibrils, the molecular spacing in the nanofibrils is increased, allowing fast transport of lithium ions and offering hopes for solid-state batteries.